Perceived intensity of emotional point-light displays is reduced in subjects with ASD - Krüger, Britta; Lis, Stefanie (Journal of autism and developmental disorders, 2018)
One major characteristic of autism spectrum disorder (ASD) is problems with social interaction and communication. The present study explored ASD-related alterations in perceiving emotions expressed via body movements. 16 participants with ASD and 16 healthy controls observed video scenes of human interactions conveyed by point-light displays. They rated the valence of the depicted emotions in terms of their intensity and judged their confidence in their ratings. Results showed that healthy participants rated emotional interactions displaying positive emotionality as being more intense and were more confident about their ratings than ASD subjects. Results support the idea that patients with ASD have an altered perception of emotions. This extends research on subjective features (intensity, confidence) of emotion perception to the domain of emotional body movements and kinematics.